Analysis of the Influence of Islamic Microfinance in Creating Sustainable Financing Model Innovations for MSMEs in Indonesia - Niken Baramurti Evieta Enggar Sandy; Sheema Haseena Armina (Iqtishodia: Jurnal Ekonomi Syariah, 2023)
One of the points of the program of Sustainable Development Goals is no poverty. Indonesia has several programs to alleviate this poverty problem as a country with high poverty. One of them is the development of MSMEs. The realization of MSMEs in Indonesia is not without problems, which in this case, is the problem of financing for business capital. This paper examines the influence of Islamic Microfinance in creating innovative sustainable financing models for MSMEs in Indonesia. The discussion in this paper offers innovations in sustainable financing, and capital models carried out by Islamic Microfinance Institutions for increasing MSMEs in Indonesia. This research uses the descriptive qualitative method. The results of this study indicate that sustainable financing initiated by Islamic Microfinance Institutions has a significant role in increasing MSMEs in Indonesia. This will also help increase state income through MSMEs and helping to alleviate poverty in Indonesia.